Regulation of emergency granulopoiesis during infection - Paudel, Sagar; Ghimire, Laxman; Jin, Liliang; Jeansonne, Duane; Jeyaseelan, Samithamby (Frontiers in Immunology, 2022)
During acute infectious and inflammatory conditions, a large number of neutrophils are in high demand as they are consumed in peripheral organs. The hematopoietic system rapidly responds to the demand by turning from steady-state to emergency granulopoiesis to expedite neutrophil generation in the bone marrow (BM). How the hematopoietic system integrates pathogenic and inflammatory stress signals into the molecular cues of emergency granulopoiesis has been the subject of investigations. Recent studies in the field have highlighted emerging concepts, including the direct sensing of pathogens by BM resident or sentinel hematopoietic stem and progenitor cells (HSPCs), the crosstalk of HSPCs, endothelial cells, and stromal cells to convert signals to granulopoiesis, and the identification of novel inflammatory molecules, such as C/EBP-β, ROS, IL-27, IFN-γ, CXCL1 with direct effects on HSPCs. In this review, we will provide a detailed account of emerging concepts while reassessing well-established cellular and molecular players of emergency granulopoiesis. While providing our views on the discrepant results and theories, we will postulate an updated model of granulopoiesis in the context of health and diseases.